Psycochemical and Sunscreen Activity Analysist of Nanocream Kepok Banana Corm - Andini Andini; Sentot Joko Raharjo; Misgiati Misgiati; Aqidatul Izza; Salsabila Putri Anugerah (Asosiasi Riset Ilmu Kesehatan Indonesia, 2024)
This study aimed to explore the potential of kepok banana pseudostem extract formulated as a nano-cream for its sunscreen properties. The sunscreen efficacy was evaluated in vitro using UV-Vis spectrophotometry to determine SPF values based on Mansur's equation. The nano-cream formulation was optimized through organoleptic evaluation, homogeneity testing, pH measurement, cream type classification, spreadability, adhesion, and particle size analysis, ensuring its stability and suitability for topical use. The results showed that the nano-cream formulations exhibited SPF values of FI 2.2018, FII 2.6646, and FIII 2.7883, with all physical parameters within acceptable limits. The particle size analysis (PSA) results on the nano-cream also revealed that the sample contained particles with an extremely small size range. This study underscores the need for further research to refine the formulation and assess its long-term stability for potential pharmaceutical and cosmetic applications.